Report on ten focus groups conducted for the 'difficult forms' NAO report - Bastow, S; Boucek, F; Campbell, R; Dunleavy, P; Margetts, H (Oxford Internet Institute, 2003)
Between December 2002 and March 2003, a team from LSE Public Policy Group and the School of Public Policy at University College, London carried out ten focus groups and a set of qualitative interviews in London, Leeds and Edinburgh to investigate how citizens used six major UK government forms. The groups formed part of a ‘value for money’ study carried out for the National Audit Office and published by them as Difficult Forms: How government agencies interact with citizens (London, The Stationary Office, 2003), HC 1145 Session 2002-2003, published 31 October 2003. The report can be downloaded free from the Publications pages of www.nao.gov.uk or from the site at www.GovernmentOnTheWeb.org which is run jointly by LSE and UCL.